2022
DOI: 10.1002/ps.6922
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and molecular characterization of Bacillus thuringiensis subsp. kurstaki toxic to lepidopteran pests Spodoptera spp. and Plutella xylostella

Abstract: Background: Bacillus thuringiensis (Bt) has been widely used as a biological control agent for lepidopteran pests. However, resistance to Bt is a major concern associated with Spodoptera spp. (Noctuidae) and Plutella xylostella (Plutellidae). For efficient control of Noctuidae and Plutellidae, novel Bt strains which have high toxicity and a broad host range are needed.Results: To develop novel Bt strains as used for bio-insecticides, the Bt IMBL-B9 with high toxicity against Spodoptera exigua, Spodoptera frugi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 56 publications
1
3
0
Order By: Relevance
“…The toxicities of B6 and P6 strains reported in this study were higher than those of the 2 reported Btk strains. Thus, our study supports previous research and demonstrates that Btk has a high insecticidal effect against S. exigua (Moar et al 1990, Hosseinzadeh et al 2016, Park et al 2022). Furthermore, previous studies have shown the toxicity of commercial Btk (53,000 SU/mg, Delfin, WG) to S. litura , with an LC 50 of 633 g/ml (Devi et al 2021).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The toxicities of B6 and P6 strains reported in this study were higher than those of the 2 reported Btk strains. Thus, our study supports previous research and demonstrates that Btk has a high insecticidal effect against S. exigua (Moar et al 1990, Hosseinzadeh et al 2016, Park et al 2022). Furthermore, previous studies have shown the toxicity of commercial Btk (53,000 SU/mg, Delfin, WG) to S. litura , with an LC 50 of 633 g/ml (Devi et al 2021).…”
Section: Discussionsupporting
confidence: 92%
“…In this study, we evaluated the insecticidal activity of 15 culturable bacterial strains isolated from naturally infected insect cadavers against second-instar larvae of laboratory-reared lepidopteran pests. Currently, Bt strains can be tentatively identified by esterase type, and by physiological and biochemical reactions (Ramya et al 2016, Li et al 2022, Park et al 2022). Most of the isolated strains showed catalase amylohydrolysis and indole properties (Table 2), which are consistent with the physiological and biochemical characteristics of Bt subsp.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations